The structure of sex differences in preferences for long-term and short-term mates - Hromatko, Ivana; Tadinac, Meri (2004)
The existence of sex differences in preferences of certain characteristics of a potential mate is well established, while their structure was not sufficiently explored. Therefore, the aim of this internet-based study was to identify the structure of sex differences in human mate preferences, depending on the type of relationship the participants are currently looking for. 2657 heterosexual subjects (939 males and 1616 females) completed the questionnaire which requested their biographical data, including age, sex, marital status, income, education, etc., their current preference for a long-term vs. short term relationship, as well as their ratings of importance and desirability of 18 characteristics of a potential mate (drawn from the Buss et al., 1990 study) on a four-point scale. Two separate discriminant analyses were performed in order to establish whether the structure of sex differences differs between subjects seeking short-term vs. long-term relationship. As predicted, the mate characteristics mostly contributing to the differentiation between sexes were not the same in the group of long-term relationship seekers as in the group of short-term relationship seekers.
Projekt MZOS
ENG